TINJAUAN BERBAGAI PENDEKATAN DAN MODEL PENGEMBANGAN KURIKULUM PAUD - Fajzrina, Lati; Amalia Rabiatul Adwiah; Sukiman (Institut Agama Islam Negeri Bone, 2025)
As is known in the world of education, the curriculum is the heart which is the main point of all its aspects (components). This research examines various reference sources such as journal articles, books, websites and other documents, therefore it is said to be a literature study. The results presented are that there are various types of approaches to implementing the curriculum, namely: academic subject, humanistic, social reconstruction, competency, systems approach, value clarification, comprehensive, integrated, technological, and problem-centered. As well as curriculum development models including: administrative (line staff) or top down, grass roots, demonstrations, beauchamp, taba, roger, systematic action research, emerging technical, tyler, wheeler, nicolls, skilbeck, and oliva. Based on the many types of approaches and models of curriculum development, school institutions are given the authority to be able to choose and develop which types and models will be applied according to the conditions of the institution (internal, external), the needs of students as well as geographical, environmental and Public.